OPTIMALISASI PENGELOLAAN KEUANGAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) MELALUI EDUKASI PERHITUNGAN KEWAJIBAN ADAT DI DESA PULAU RAJA KABUPATEN BANYUASIN - Riani Widyaswara; Rena Syilvia; Rusmini; Andi Candra; Ogi Meita Utami (Sumpah Pemuda : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program was conducted to improve the understanding of MSME actors in Pulau Rajak Village, Banyuasin Regency, regarding the importance of simple and measurable financial management, particularly in fulfilling customary obligations within the community. MSME actors often face difficulties in separating business income, operational costs, household needs, and social or customary obligations. This condition may affect business sustainability when customary obligations are not calculated based on proportional economic capacity. This program aims to provide education on how to calculate income, expenses, net profit, and fund allocation for customary obligations in a simple manner. The methods used include counseling, interactive discussion, financial calculation simulations, and evaluation of participants’ understanding. The results show an increase in participants’ understanding of financial recording, separation of business capital and personal needs, and the calculation of customary obligations based on real economic capacity. This program is expected to help MSME actors maintain a balance between respect for customary values and business sustainability.